Dampak Pengaruh Digitalisasi Era Society 4.0 Terhadap Manajemen Kinerja Pegawai - Awaluddin Awaluddin (Syntax Corporation Indonesia, 2023)
In the Society 4.0 era marked by digitalization, the development of information technology has changed the way of work, communication, and management in various sectors, including the government and business sectors. This study aims to determine the impact of digitalization in the Society 4.0 era on employee performance management. This research uses qualitative research methods. The data collection technique was carried out by literature study by exploring journals, books and other information relevant to the research. The data that has been collected is then analyzed with three stages, namely data reduction, data presentation and conclusion drawing. The results showed that the digitalization of the Society 4.0 era has positive and negative impacts on employee performance management. The positive impact of digitization in the Society 4.0 era on employee performance management includes increasing the efficiency and effectiveness of employee performance management, increasing the objectivity of employee performance appraisals, increasing transparency and accountability of employee performance management, increasing employee motivation and job satisfaction. Meanwhile, the negative impacts of digitization in the Society 4.0 era on employee performance management include increasing the complexity of employee performance appraisals and increasing information security risks.